Human factors challenges for the safe use of artificial intelligence in patient care. Issue 1 (27th November 2019) - Sujan, Mark; Furniss, Dominic; Grundy, Kath; Grundy, Howard; Nelson, David; Elliott, Matthew; White, Sean; Habli, Ibrahim; Reynolds, Nick
Abstract : The use of artificial intelligence (AI) in patient care can offer significant benefits. However, there is a lack of independent evaluation considering AI in use. The paper argues that consideration should be given to how AI will be incorporated into clinical processes and services. Human factors challenges that are likely to arise at this level include cognitive aspects (automation bias and human performance), handover and communication between clinicians and AI systems, situation awareness and the impact on the interaction with patients. Human factors research should accompany the development of AI from the outset.